Providing Explicit Language Instruction to Assist Students’ Language Learning in EFL Classrooms - Suci Noer Wulan Sari (Indonesian Journal of EFL and Linguistics, 2018)
In language teaching process, instruction becomes one of important things to provide in order to encourage students’ language learning. Since the late 1960s, one of the language instructions that has been available is explicit language instruction which is believed as one of useful tools for the teaching practice. Given that the present study tried to investigate how English lecturers provide explicit language instruction in EFL classrooms to assist their students’ language learning. To gain the data, a case study employing semi-structured interviews and classroom observations were conducted. Two English lecturers were purposively selected to be the participants of the study for their familiarity of the instruction. Based on the analysis, the study revealed some of the elements of explicit language instruction provided such as clearly stating the lesson’s objectives and teachers’ expectations, using language clearly and concisely, providing step-by-step demonstrations and adequate examples, guiding students through practices on language functions, monitoring student performance and responses by giving feedbacks, and encouraging students to organize knowledge.  It can be concluded that explicit language instruction actually can be considered for classroom improvement. Future studies are suggested to investigate students’ voices of the implementation of the instruction that may actually help their lecturers better their teaching practices and favour their students’ learning outcomes.